Interconversion of stereochemically labile enantiomers (enantiomerization) - Trapp, Oliver (Differentiation of enantiomers II, 2013)
The investigation of the molecular dynamics of stereoisomers is of fundamental interest in chemistry, biochemistry, medicine, and related areas. In recent years enantioselective dynamic chromatography and enantioselective dynamic capillary electrophoresis (DCE) have been established as versatile tools to investigate the kinetics of interconversions of stereoisomers. The term dynamic chromatography and dynamic electrophoresis, following the term dynamic NMR (DNMR) (Grathwohl and Wüthrich, Biopolymers 20:2623-2633, 1981; Wüthrich, Angew Chem Int Ed 42:3340-3363, 2003; Binsch et al., Angew Chem Int Ed 10:570-572, 1971), stresses the dynamic (Herschbach, Angew Chem Int Ed 26:1221-1243, 1987) behavior of analytes to interconvert between two stereoisomeric forms during the separation process. If the interconversion process is slow compared to the separation of the enantiomers, which can be achieved by accelerating the separation process or lowering the temperature, partial separation with characteristic plateau formation or peak broadening is observed.This chapter gives an overview of recent advances in the study of stereodynamics of molecules by dynamic chromatography (Trapp et al., Chirality 13:403-414, 2001; D’Acquarica et al., J Sep Sci 29:1508-1516, 2006; Wolf, Chem Soc Rev 34:595-608, 2005; Wolf, Dynamic stereochemistry of chiral compounds - principles and applications. RSC Publishing, Cambridge, 2008) and capillary electrophoresis. Models and algorithms to evaluate interconversion profiles obtained by separation techniques are discussed with respect to the challenging demands of high separation efficiencies typical of modern separation techniques. Models used for evaluation are based on iterative computer simulation algorithms using the theoretical plate model (TPM) or stochastic model of chromatography, empirical calculation methods, derived from equations used in chemical engineering, namely Damköhler analysis, and direct access using the approximation function, and more recently the unified equation of chromatography, which can be applied to all kinds of first-order reactions taking place during a chromatographic or electrophoretic separation. Furthermore, areas of applications to investigate stereodynamic processes are presented and discussed to give a practical guide for using dynamic chromatography and capillary electrophoresis.
Gesehen am 10.02.2022